2007
DOI: 10.1111/j.1365-2044.2007.05295.x
|View full text |Cite
|
Sign up to set email alerts
|

Intensive care in the developing world

Abstract: Summary Appropriate and sustainable intensive care practice is possible even in the resource‐limited locations of sub‐Saharan Africa. Data from seven sub‐Saharan African countries indicates that the majority of patients served are surgical. Comparison between intensive care units is difficult due to lack of laboratory support, which precludes the severity sickness scores used internationally. Hospital mortality can be reduced by increasing nurse/patient ratios, adequate monitoring and initiating postoperative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
51
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(61 citation statements)
references
References 26 publications
8
51
2
Order By: Relevance
“…Surgical conditions constituted majority of admissions. These results are supported by results of previous studies which also reported that most of the patients admitted to ICU in the developing world were surgical cases [4] [5]. In light of this growing evidence, there is need for strengthening surgical care in these countries to reduce the burden of surgical diseases on critical care services.…”
Section: Discussionsupporting
confidence: 78%
“…Surgical conditions constituted majority of admissions. These results are supported by results of previous studies which also reported that most of the patients admitted to ICU in the developing world were surgical cases [4] [5]. In light of this growing evidence, there is need for strengthening surgical care in these countries to reduce the burden of surgical diseases on critical care services.…”
Section: Discussionsupporting
confidence: 78%
“…A similar finding was reported by other studies of ICUs in sub Saharan Africa as there was a predominantly young-age ICU population (Okafor, 2009;Ohaegbulam et al, 2007;Mhando et al, 2008;Jamison et al, 2006). Similarly, the patient population in this study is younger when compared with patients admitted to ICUs in most developed world (Moran et al, 2008;Towey and Ojara, 2007). The overall young population and male predominance in this study may be because of high prevalence of trauma which likely occurred due to the nature of work exposing majority of males on urban streets or the increased level of participation in high-risk activities among male individuals and higher working age male predominance (Towey and Ojara, 2007).…”
Section: Discussionmentioning
confidence: 58%
“…Similarly, the patient population in this study is younger when compared with patients admitted to ICUs in most developed world (Moran et al, 2008;Towey and Ojara, 2007). The overall young population and male predominance in this study may be because of high prevalence of trauma which likely occurred due to the nature of work exposing majority of males on urban streets or the increased level of participation in high-risk activities among male individuals and higher working age male predominance (Towey and Ojara, 2007). This study also revealed that about 46.42% of patients admitted to ICU died which is higher than a study conducted in University of Nigeria Teaching Hospital on neurological and obstetric patients of which the mortality rates were 43.5 and 33%, respectively (Okafor and Onwuekwe, 2004a;Okafor and Aniebue, 2004b).…”
Section: Discussionmentioning
confidence: 75%
“…The impact of such analysis could be stronger in limited resource countries, where the burden of expensive critical care is relevant both to the hospital and to the patient. These scoring systems include physiological and laboratory indicators which usually are not available in African settings, thus, comparing the quality of care in different countries, or care before and after intervention, becomes a difficult task, given the difficulty in standardising severity of illness [5]. As in many other Track and Trigger warning systems, the introduction of MEWS was aimed at quickly recognising patients with potential or established critical illnesses, and to assure appropriate care by skilled staff in a proper setting (ICU).…”
Section: Discussionmentioning
confidence: 99%